PENANAMAN KEMANDIRIAN ANAK USIA 4-5 TAHUN BERBASIS METODE PROYEK DI PAUD VIDYA KARUNA KOTA DENPASAR - Silvia Nina Sany; I Wayan Suyanta; I Made Lestiawati (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2022)
The prolonged pandemic period forces children to lose their learning period at school. There are many obstacles, especially learning in early childhood. Teachers are expected to be able to provide a comfortable and fun form of learning, one of which is project-based learning methods. By applying a project-based approach at PAUD Vidya Karuna Denpasar, children get a learning experience working together, sharing tasks and responsibilities that are carried out in an integrated manner to achieve a common goal. Children understand the material when child has tried to do activities and find out solution to a problem. Focus of this research is the inculcation of children's independence based on the project method. Type of research is descriptive qualitative research with data collection techniques of observation, interviews, and documentation. The data analysis technique used is the Miles and Hubberman model with an interactive model consisting of four stages, namely data collection, data reduction, data presentation, and conclusion drawing. The results showed inculcation of children's independence through this project-based learning method increased by 40% from the initial observation. As many as 86% of children aged 4-5 years have become independent according to the indicators of the child independence instrument. Project-based learning also improve children's cognitive and socio-emotional